2012
DOI: 10.1371/journal.pone.0050456
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 3-Phenoxybenzoic Acid by a Bacillus sp

Abstract: 3-Phenoxybenzoic acid (3-PBA) is of great environmental concern with regards to endocrine disrupting activity and widespread occurrence in water and soil, yet little is known about microbial degradation in contaminated regions. We report here that a new bacterial strain isolated from soil, designated DG-02, was shown to degrade 95.6% of 50 mg·L−1 3-PBA within 72 h in mineral salt medium (MSM). Strain DG-02 was identified as Bacillus sp. based on the morphology, physio-biochemical tests and 16S rRNA sequence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
5
37
3
Order By: Relevance
“…The study of an organism's metabolic pathways is crucial for analyzing the biodegradation potential of a microorganism. Intermediate metabolites are sometimes more toxic than the parent compound [52][53][54]. We confirmed that strain SG4 produced non-toxic intermediates while effectively degrading cypermethrin.…”
Section: Discussionsupporting
confidence: 59%
“…The study of an organism's metabolic pathways is crucial for analyzing the biodegradation potential of a microorganism. Intermediate metabolites are sometimes more toxic than the parent compound [52][53][54]. We confirmed that strain SG4 produced non-toxic intermediates while effectively degrading cypermethrin.…”
Section: Discussionsupporting
confidence: 59%
“…Degradation rates of β-CY and 3-PBA by ET1 were described using During β-CY and 3-PBA degradation, three compounds, namely, 3-phenoxybenzaldehyde, phenol, and catechol, were identified as metabolites based on results of GC-MS and LC-MS analyses, which were previously detected (Chen, Hu, et al, 2012c;Deng et al, 2015;Tallur et al, 2008;Zhu et al, 2016). The results evidently showed that strain ET1 transforms β-CY through hydrolysis to yield α-cyano-3-phenoxybenzyl alcohol, which was very unstable and spontaneously rearranged into 3-phenoxybenzaldehyde followed by dehydrogenation into 3-PBA.…”
Section: Discussionmentioning
confidence: 99%
“…Heudorf et al [8] reported that 3-PBA residue in urine of children and adolescents in Germany was 0.30 μg/L. 3-PBA can also be toxic to humans through disruption of the normal secretion of reproductive hormones and breakage of sperm DNA, which lowers sperm count [911]. Therefore, it is critically necessary to degrade β-CY and 3-PBA.…”
Section: Introductionmentioning
confidence: 99%